MiR-19 targeting of PTEN mediates butyl benzyl phthalate-induced proliferation in both ER(+) and ER(−) breast cancer cells. (1st October 2018) - Wu, Jieshu; Jiang, Ye; Cao, Wanshuang; Li, Xiaoting; Xie, Chunfeng; Geng, Shanshan; Zhu, Mingming; Liang, Zhaofeng; Zhu, Jianyun; Zhu, Weiwei; Wu, Rui; Ma, Xiao; et al.
Highlights: BBP triggered proliferation of ER(+) MCF-7 and ER(-) MDA-MB-231 breast cancer cells. BBP induced the expression of miR-19 and modulated PTEN/AKT/p21 axis. miR-19 mediated BBP-triggered breast cancer cell proliferation. BBP suppressed PTEN through miR-19 targeting of PTEN 3'UTR. Abstract: Breast cancer is the most common cancer among women worldwide. Butyl benzyl phthalate (BBP) is ubiquitous in human's environment, and is strongly linked to breast cancer development. microRNA (miRNA) is an important regulator of target genes. So far, no studies have been reported yet to reveal the action of miRNAs in BBP-mediated breast cancer cell proliferation. In this study, we showed that BBP induced proliferation of both ER(+) MCF-7 and ER(-) MDA-MB-231 breast cancer cells, proved by increased cell viability, transition of cell cycle from G1 to S phase, upregulation of proliferating cell nuclear antigen (PCNA) and Cyclin D1, and downregulation of p21. Meanwhile, the expression of oncogenic miR-19a/b and PTEN/AKT/p21 axis was also modulated by BBP. Furthermore, for the first time we revealed that miR-19 played crucial role in the promoting effect of BBP on breast cancer cells through targeting PTEN 3'UTR. Findings from this study could provide an important new perspective on the molecular mechanisms through which BBP exerts its promoting effect on breast cancer as well as its target intervention.